Business Plan of Bimtube Hotel / Nur Ain Sabrina Saparin...[et al.] - Saparin, Nur Ain Sabrina; Hamidun, Nur Anis Atikah; Amrul Hizal, Nur Asheera Awatif; Mohamad Rizal, Nor Erni Eliyana; Mohammat Nazari, Nur Hidayah (2020)
The name of the business is Bim Enterprise and we offer BimTube Hotel. Bim stands for Bring in Memories. The idea of getting the name of the company is because we want to create and share the great memories of our customer throughout their journey while staying in our BimTube. The business nature of BimTube is hotel services and accommodation. Bim Enterprise expect to catch the interest of loyal customer with providing high quality services. We are using tube concept with the combination of modern and nature style to operate our business as it is unique from other hotel industry in Malaysia. Bim Enterprise is located at Pantai Chenang, Langkawi. The reason of choosing this location is because it is a strategic location as it is the center of tourism and near to the facilities. This business will be highly demanded as our customer can enjoy modern contemporary style hotel and nature environment because we are located near the beach. Our target is to create modern inn lifestyle that bring in memories and give warm hospitality to the customer. BimTube Hotel will start operate in June 2020. According to research of tourism Malaysia website, total expenditure by domestic tourist registered a double-digit growth of 11.7%, recording a total of RM 60.4 billion as compared to RM 54.1 billion in 2017. This is the reason why we choose this high revenues services as our proposed business.